Madrid on the move : feeling modern and visually aware in the nineteenth century - Rodríguez-Galindo, Vanesa (Interventions: rethinking the nineteenth century (Series), 2021)
Madrid on the move offers an account of illustrated print culture and the urban experience in nineteenth-century Spain. It provides a fresh account of modernity from a transnational perspective. Drawing on different kinds of printed images and texts, the book explores what being modern meant to people in their daily lives.